B7-H3 inhibits the IFN-γ-dependent cytotoxicity of Vγ9Vδ2 T cells against colon cancer cells. (1st January 2020) - Lu, Huimin; Shi, Tongguo; Wang, Mingyuan; Li, Xiaomi; Gu, Yanzheng; Zhang, Xueguang; Zhang, Guangbo; Chen, Weichang
ABSTRACT: The immunoregulatory protein B7-H3, a member of the B7 family, has been confirmed to be highly expressed in colon cancer. However, the exact influence of B7-H3 on the features and antitumor ability of γδT cells in colon cancer remains unknown. In the present study, we investigated that the proportions of B7-H3 + γδT cells were distinctly increased in the peripheral blood and tumor tissues of colon cancer patients. B7-H3 blockade or knockdown promoted proliferation, inhibited cell apoptosis and induced the expression of activation markers (CD25 and CD69) on Vδ2 T cells. In contrast, treatment with the B7-H3 agonist 4H7 had the opposite effect. Furthermore, B7-H3 suppressed IFN-γ expression by inhibiting T-bet in Vδ2 T cells. Moreover, B7-H3 mediated the inhibition of Vδ2 T cell cytotoxicity via the downregulation of IFN-γ and perforin/granzyme B expression. More importantly, blocking the B7-H3 function significantly enhanced the cytotoxicity of Vδ2 T cells against colon cancer cells in vivo. Therefore, the inhibition or blockade of B7-H3 is a potential immunotherapeutic approach for colon cancer.